2004
DOI: 10.1186/1471-2490-4-15
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive analysis of urinary calculi using micro computed tomography

Abstract: BackgroundMicro computed tomography (micro CT) has been shown to provide exceptionally high quality imaging of the fine structural detail within urinary calculi. We tested the idea that micro CT might also be used to identify the mineral composition of urinary stones non-destructively.MethodsMicro CT x-ray attenuation values were measured for mineral that was positively identified by infrared microspectroscopy (FT-IR). To do this, human urinary stones were sectioned with a diamond wire saw. The cut surface was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 21 publications
3
72
0
Order By: Relevance
“…The present study is a refinement of this approach, utilizing the powerful ability of CT to display the internal structure of urinary stones [18,20]. The results demonstrate that COM stones that show visible structure on CT are more fragile to SW's than COM stones that appear to be homogeneous in their structure (Figure 3).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The present study is a refinement of this approach, utilizing the powerful ability of CT to display the internal structure of urinary stones [18,20]. The results demonstrate that COM stones that show visible structure on CT are more fragile to SW's than COM stones that appear to be homogeneous in their structure (Figure 3).…”
Section: Discussionmentioning
confidence: 77%
“…Each stone was scanned with a Scanco mCT20 micro CT system (voxel size from 18 to 34 μm) to verify composition [20] (found to be 98±4% pure COM, mean ±s.d., for 47 stones) and also for assessment of heterogeneity (presence of pronounced lobulation, voids, or apatite inclusions) by four blinded observers (method described below). Stones were weighed dry, and a mean diameter of each stone was calculated from the stone volume found by micro CT, assuming a spherical shape for the stone.…”
Section: Methodsmentioning
confidence: 99%
“…After the completion of the experiment, the stones were dried, and evaluation of the internal structure of all stones was performed using micro CT. Each stone was scanned on a Scanco mCT20 micro-CT system (Scanco Medical AG, Bassersdorf, Switzerland) with 18-μm isotropic voxel size and assessed for stone composition, as previously described (17). The goal of this additional characterization was to find out if any of the stones previously identified by infrared spectroscopy as "pure" showed evidence of a mixed composition.…”
Section: Methodsmentioning
confidence: 99%
“…The goal of this additional characterization was to find out if any of the stones previously identified by infrared spectroscopy as "pure" showed evidence of a mixed composition. Examples of micro-CT sections of the stones used in this study are shown in Fig 4. For the stones with mixed composition, the volume content of each mineral component was estimated using ImageJ (a public domain image processing program) by thresholding the stone images at levels appropriate for the individual minerals (17). Stones were analyzed by micro-CT blindly; that is, the micro-CT analyses were completed without knowledge of the infrared spectroscopy data.…”
Section: Methodsmentioning
confidence: 99%
“…The micro computed tomography (micro CT) as a potential method for the analysis of urinary stone composition and morphology in a nondestructive manner at very high resolution (Zarse et al, 2004). Micro CT, which has seen considerable use as a research tool in bone biology (Ruegsegger et al, 1996), has the ability to reconstruct 2-D and 3-D images of urinary stones that allow the 3-D image of the stone to be cut and viewed in multiple planes with voxel sizes of 8-34 μm.…”
Section: Imaging Investigationsmentioning
confidence: 99%